Accelerated alkaline activation of peroxydisulfate by reduced rubidium tungstate nanorods for enhanced degradation of bisphenol A. Issue 11 (8th October 2020) - Hu, Jian; Zeng, Xiangkang; Yin, Yichun; Liu, Yue; Li, Yang; Hu, Xiaoyi; Zhang, Lian; Zhang, Xiwang
Abstract : Reduced rubidium tungstate nanorods were employed to activate peroxydisulfate under alkaline conditions for bisphenol A degradation. Abstract : Persulfate-based advanced oxidation processes have demonstrated great prospects in engineering applications for environmental remediation. However, most of these processes are only effective under neutral or acidic conditions, and there are still very few studies on the alkaline activation of persulfate for the removal of contaminants. In this study, reduced rubidium tungstate (rRT) nanorods were synthesised and employed to activate peroxydisulfate (PDS) under alkaline conditions to effectively remove bisphenol A (BPA), a crucial pollutant in aqueous systems. It is confirmed that the rRT nanorods exhibited a superior BPA degradation rate (0.0173 min −1, 150 min) at the pH value of 11.0 compared to pH 7.0 (0.0009 min −1, 150 min) and pH 3.0 (0.0004 min −1, 150 min). The quenching test and chemical probes further unveiled that the superoxide (O2 ˙ − ) radical rather than sulfate radical (SO4 ˙ − ) and hydroxyl radical (˙OH) acted as the primary reactive oxygen species (ROSs); it was also preferentially formed under alkaline conditions. This is mainly because the electron transfer efficiency was remarkably enhanced between rRT nanorods and PDS in the alkaline rRT/PDS system, as supported by the electrochemical characterizations and X-ray photoelectron spectroscopy (XPS) analysis. This study provides new insights into the development of alkaline persulfate-activation catalysts for industrial wastewater treatment.